Assessing the sustainability of Maltese government debt - John Farrugia; Owen Grech (Central Bank of Malta, 2013)
This study discusses the concept of fiscal sustainability and, by so doing, sheds light on government debt dynamics. It then presents a conventional debt sustainability analysis (DSA) exercise to gauge the sustainability of Maltese general government debt over the medium to long term. The exercise consists of two alternative scenarios which reveal how the government debt-to-GDP ratio might evolve over the next decade. For robustness, each scenario is subjected to a number of adverse shocks. The results suggest that Maltese government debt is sustainable, but this comes with important caveats.
Keywords: H63; H68; 330